Análise do roubo de eletricidade e a propagação de sua influência usando redes multiplexadas e heterogêneas - Borro, Luiz C.; Maioli, Mayara C.; Souza, Tales F. B.; Pinto, Daniel C. (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM); 2019: Anais do VIII Brazilian Workshop on Social Network Analysis and MiningDO - 10.5753/brasnam.2019.6543, 2019)
In developing countries, electricity theft is a common type of non- technical losses (NTL, i.e., losses associated with electricity that is consumed but not billed by some type of anomaly), financially affecting not only distribution system operators (DSO) but also customers. Similarly to frauds in other contexts, there is evidence that electricity theft is highly influenced by social interactions. Here we propose a multiplex and heterogeneous network model to evaluate how social and professional interactions influence on electricity theft. Particularly, by employing a variation of the random walk with restart algorithm we were able to derive a new exposure score for discriminating between fraudsters and regular customers.